Responding to Local Needs by Mobilizing Community Assets: Age-Friendly Community Initiatives During the COVID-19 Pandemic. (19th May 2022) - Greenfield, Emily A; Pestine-Stevens, Althea; Scher, Clara
Abstract: Background and Objectives: Age-friendly community initiatives (AFCIs) strive to make localities better for long and healthy lives by fostering improvements across social, physical, and service environments. Despite the heightened need for community supports during the coronavirus disease 2019 pandemic, very little research has addressed the work of AFCIs in the context of this crisis. We aimed to develop theory on how AFCI core teams have contributed to community responses during the pandemic, as well as what contexts have influenced the initiatives' ability to contribute. Research Design and Methods: As part of a multiyear, community-partnered study on the development of philanthropically supported initiatives in northern New Jersey, we conducted qualitative interviews with 8 AFCI core teams during the winter of 2020–2021. The interviews focused on the leaders' efforts at that time, with probing questions concerning enabling factors for their community responses. We analyzed the data using an inductive coding process encompassing open, axial, and subcoding. Results: The analysis indicated four distinct roles of AFC core groups: good community partner, creator, advocate, and communications broker . We further found that AFC leaders primarily drew on three types of capital—human, social, and tangible—to enact these roles, oftentimes in cumulative ways. Discussion and Implications: We interpret our study's findings and their implications by integrating insights from theories of social impact. We further highlight the importance of continued research on community-centered approaches to promote aging in community during times of societal crisis, and otherwise.